An appraisal of the implementation of the English language syllabus for French-speaking learners in Cameroon - Talba, Baissana; Paschal, Mahona Joseph (S&Co Publishing, 2023)
The present paper set out to investigate the effectiveness of the implementation of the English Syllabus for French-speaking learners in some secondary schools in the Diamaré, Mayo Kani, and Mayo Tsanaga Divisions in the Far-North Region of Cameroon. The target schools were GBHS Maroua, GBHS Kaele, and GBHS Mokolo. The main assumption was that the English language curriculum is not well implemented in the target schools. The study was carried out on a sample of 152 students, nine (09) English teachers and three (03) pedagogic inspectors. The instruments used for the collection of quantitative and qualitative data were questionnaire and interview, respectively. After the analysis of the data, the findings revealed the English language syllabus was appropriate in terms of goals, contents, and methods. However, teachers did not use the adequate methods suggested by the syllabus in their respective classrooms and they had negative attitudes toward the implementation of the syllabus. Moreover, some external and internal factors hinder the implementation of the syllabus. Thus, the English syllabus was not well implemented in those target schools. The study also made some recommendations for the good implementation of the syllabus by teachers such as the follow-up of teachers by the pedagogic inspectors to keep the former abreast with new approaches and methods; the incorporation of listening and oral skills in the examinations, and the provision of schools’ libraries with the adequate resources and internet facilities.